FINANCIAL DISTRESS AND FINANCIAL SUSTAINABILITY: PANEL EVIDENCE FROM INDONESIAN NON-FINANCIAL FIRMS - Ikin Solihin; Cindy Rahmawati Raihanah (Faculty of Economics and Business Universitas Pelita Harapan, 2026)
Financial sustainability is a fundamental pillar of long-term corporate viability; however, it remains underexplored within the broader sustainability discourse, which is often dominated by environmental and social dimensions. This study aims to bridge this gap by examining financial distress as a key indicator of financial resilience and sustainable business continuity in emerging markets. Using panel data from 416 Indonesian non-financial firms over the period 2013–2022, this study employs a logistic regression approach to analyze the impact of profitability, liquidity, leverage, operating cash flow, and firm size on the likelihood of financial distress. Financial distress is defined based on the interest coverage ratio, where firms with a ratio below one are classified as distressed. The empirical results reveal that profitability is the only statistically significant determinant of financial distress, highlighting its dominant role in sustaining firm operations. In contrast, liquidity, leverage, operating cash flow, and firm size do not exhibit significant effects, suggesting that traditional financial indicators may have limited predictive power in the Indonesian context. These findings emphasize the importance of profitability-driven resilience as a core component of financial sustainability in emerging markets. This study contributes to the literature by repositioning financial distress within the financial sustainability framework and providing empirical evidence from a large panel dataset in Indonesia. The results offer practical implications for investors, creditors, and policymakers in developing more effective early warning systems and strengthening financial resilience as a foundation for sustainable business practices.